Health priorities in a changing climate - Thomson, Madeleine; Rabie, Tamer Samah; Shumake-Guillemot, Joy; McDermott, John; James, Wilmot; Wannous, Chadia (Routledge, 2018)
This chapter discusses some of the major policy drivers that have shaped, and aims to affect, international and national strategies where health and climate intersect. It focuses on the opportunities created for climate information and associated services to support public health decision-making in a changing climate. Globalization is at the heart of this process, which is both driving, and subject to, accelerating global environmental and climate change. Climate interacts with health through a wide variety of direct and indirect mechanisms. Floods, for example may directly lead to deaths through drowning, and can result in an increase in diarrhoeal and vector-borne diseases. They can also have a significant impact on food production, leading to increases in food prices and consequent reductions in household nutrition. Indirect social and economic impacts of climate and weather shocks may drive households into poverty, which is in itself a major determinant of poor health.